2021
DOI: 10.1136/bmjopen-2021-049307
|View full text |Cite
|
Sign up to set email alerts
|

Association between renal function and cardiovascular mortality: a retrospective cohort study of elderly from health check-up

Abstract: ObjectivesThis study aimed to investigate the relationship between cardiovascular mortality in elderly Asians and decline in renal function.DesignA retrospective cohort study.SettingCommunity-based health examination database from Taipei city.ParticipantsAt the beginning, the database included 315 045 health check-up visits of 97 803 elderly persons aged ≥65 years old from 2005 to 2012. After excluding missing values and outliers, there were 64 732 elderly persons with at least two visits retained for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(68 reference statements)
0
3
0
1
Order By: Relevance
“…Preoperative RD was defined by the preoperative EGFR. CKD stage 3a (45 ≤ EGFR < 60 mL/min/1.73 m 2 ) or higher according to KDIGO CKD guideline is reportedly associated with an increase in the risk of various diseases and mortality[ 18 - 20 ], so the RD group comprised patients with an EGFR < 60 mL/min/1.73 m 2 , and the non-RD group comprised patients with an EGFR ≥ 60 mL/min/1.73 m 2 . Moreover, we also categorized patients into three groups according to the RD as defined by the EGFR (severe CKD, EGFR < 30 mL/min/1.73 m 2 ; mild CKD, 30 ≤ EGFR < 60 mL/min/1.73 m 2 ; control, EGFR ≥ 60 mL/min/1.73 m 2 ) because patients with ESRD who were undergoing dialysis were likely to be at high risk of developing HCC[ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative RD was defined by the preoperative EGFR. CKD stage 3a (45 ≤ EGFR < 60 mL/min/1.73 m 2 ) or higher according to KDIGO CKD guideline is reportedly associated with an increase in the risk of various diseases and mortality[ 18 - 20 ], so the RD group comprised patients with an EGFR < 60 mL/min/1.73 m 2 , and the non-RD group comprised patients with an EGFR ≥ 60 mL/min/1.73 m 2 . Moreover, we also categorized patients into three groups according to the RD as defined by the EGFR (severe CKD, EGFR < 30 mL/min/1.73 m 2 ; mild CKD, 30 ≤ EGFR < 60 mL/min/1.73 m 2 ; control, EGFR ≥ 60 mL/min/1.73 m 2 ) because patients with ESRD who were undergoing dialysis were likely to be at high risk of developing HCC[ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies found that accelerated decline in kidney function was associated with high uric acid levels, high blood pressure, and metabolic syndrome [ 7 9 ]. Also, rapid deterioration in kidney function is strongly associated with increased complications, cardiovascular events, and all-cause mortality [ 10 ]. Uric acid is the end product of purine metabolism in the human body, and it exhibits antioxidant activities within the normal physiological range [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More severe CKD increases the risk of adverse clinical outcomes, in particular cardiovascular disease (CVD) and mortality [6,7], and necessitates more intensive and more expensive therapy, including renal replacement therapy (RRT) such as dialysis or kidney transplant [8]. For example, among commercially insured US patients with CKD, microalbuminuria, and T2DM, per-person per-year costs were USD 18,529 in patients with CKD stage 1, compared with USD 110,210 in patients with CKD stage 5 [4].…”
Section: Introductionmentioning
confidence: 99%